Investigation of some Philippine plants for antimicrobial substances - Masilungan, Victoria A.; ela Cruz, Roseanna M.; Ramos Edna V. (1976)
The antimicrobial activity of 848 extracts prepared from 106 species of Philippine plants belonging to 44 families was determined by the disc agar diffusion method of assay. Eight solvents (ether, petroleum ether, acetone, alcohol, benzene, chloroform, water and 1 per cent sodium bicarbonate) were used to extract substances from each plant Of the plants tested, 62 or 58 per cent were shown to contain substances inhibitory to Bacillus subtilis, Micrococcus aureus, Escherichia coli and Mycobacterium tuberculosis 607. The highest incidence of antimicrobial activity was obtained with alcohol extractions followed by ether, acetone, water, benzene, chloroform, 1 per cent sodium bicarbonate and petroleum ether in this order. The 9 most active plants which demonstrated exceptionally high values of antimicrobial activity are :Alphonsea arborea, Alstonia scholaris, Artocarpus blancoi, Caesalpinia crista, Callicarpa formosana, Diplodiscus paniculatus, Pisonia umberllifera, Talauma villariana and Zingiber officinale. The occurence of antimicrobial principles in some plants of India, Canada, Australia, America, Japan and Taiwan have been reported as early as man's search for natural sources of remedial cures for diseases. A number of Philippine plants were also screened for the presence of substances inhibitory to Micrococcus aureus and Escherichia coli by Masilungan et. al. employing alcohol and water for extractions. The study presented here is an extension of in-vitro studies with the inclusion of more test organisms and more solvents for extracting active substances. This report deals.
Includes bibliographical references (pages 212-213)
Keywords: Biological Sciences; Plants, Philippine -- Antimicrobial properties